Immunological studies in patients with chronic active hepatitis. Cytotoxic activity of lymphocytes to autochthonous liver cells grown in tissue culture. - Paronetto, F (1975)
The cytotoxic activity of lymphocytes against autochthonous liver cells was studied in patients with chronic liver diseases and in controls. Cytotoxicity of lymphocytes was observed in eight of ten patients with chronic active hepatitis, two patients with chronic persistent hepatitis, one patient with primary biliary cirrhosis, one patient with alcoholic hepatitis and carcinoma of the pancreas, and in three of five patients with acute viral hepatitis, but not in seven patients without liver alteration or with miscellaneous liver diseases. Serum was not cytotoxic, but in three patients it decreased the cytotoxicity of lymphocytes. Cytotoxicity was seen in both HBAg-positive and HBAg-negative patients, appears to be influenced by therapy, and does not correlate with autoantibodies. These data support the hypothesis of an aggressive activity of lymphocytes in certain liver diseases.